Hermetic polysemy of water in the oneiro-iconopoems of the Surrealists Benoît and Bounoure - D’Urso, Andrea (Oltreoceano - Rivista sulle migrazioni, 2024)
This essay aims at highlighting the aquatic occurrences in some poems by the French Surrealist poet Vincent Bounoure, illustrated by the Quebecois artist Jean Benoît. Starting from a brief presentation of the latter, the article draws attention to the phenomenon of reverse emigration: rather than the well-known migration from Europe to North America, it focuses on Benoît’s choice to leave the conservative milieu of Quebec and move to Paris with his wife Mimi Parent in the late 1940s. This eastward emigration across the Atlantic was fruitful for the couple, who was welcomed into the Parisian group of the Surrealist movement, then still animated by its founder, André Breton; some years after his death, they also helped Vincent Bounoure continue the Surrealist activities, against Jean Schuster’s attempt to consider them finished in 1969. A year before Breton’s death, Benoît and Bounoure published a work entitled Envers l’ombre (1965), which consists of fourteen poems by Bounoure with some illustrations by Benoît. Our analysis will first offer some elements for an iconotextual philological reconstruction of how this work was produced, by also taking into account some unpublished documents from Bounoure’s archives. It will then offer an interpretation of those iconotexts which, either in Bounoure’s poems, in Benoît’s images or in both, evoke some references to water. Attention will be focused, in particular, on the hermetic interpretative clue indispensable for the polysemic understanding of these watery references in Bounoure’s poems and their analogical transfiguration in Benoît’s illustrations; finally, we propose to call these texts “oneiric iconopoems”.